2022
DOI: 10.1017/s0014479722000199
|View full text |Cite
|
Sign up to set email alerts
|

Starch granule size in grains of hybrid rice with low chalkiness occurrence

Abstract: Summary The occurrence of chalkiness has decreased in new hybrid rice cultivars in China. As both chalkiness occurrence and starch granule size are associated with the biosynthesis of starch, we hypothesized that there may be a correlation between chalkiness occurrence and starch granule size, and this may partially explain the decreased chalkiness occurrence in the new hybrid rice cultivars. To test this hypothesis, a field experiment was conducted over eight environments (two years × four sowing dates) wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
(25 reference statements)
0
2
0
Order By: Relevance
“…Our results indicate that the CGR and CD were positively correlated with the proportions of volume (V) <10 µm, surface area (S) < 10 µm, and numbers (N) < 10 µm while the opposite, i.e., V >10 µm, S >10 µm, and N >10 µm, was observed under either the LNT or HNT. Cao et al [12] demonstrated that an increase in starch grain size helped to reduce the chalkiness of rice. HNT under the grain-filling stage led to a smaller diameter of the starch granules, which may have been related to increased α-amylase activity [48] and the inhibition of starch synthase [49].…”
Section: Correlation Between Chalkiness and The Structural Thermal An...mentioning
confidence: 99%
See 1 more Smart Citation
“…Our results indicate that the CGR and CD were positively correlated with the proportions of volume (V) <10 µm, surface area (S) < 10 µm, and numbers (N) < 10 µm while the opposite, i.e., V >10 µm, S >10 µm, and N >10 µm, was observed under either the LNT or HNT. Cao et al [12] demonstrated that an increase in starch grain size helped to reduce the chalkiness of rice. HNT under the grain-filling stage led to a smaller diameter of the starch granules, which may have been related to increased α-amylase activity [48] and the inhibition of starch synthase [49].…”
Section: Correlation Between Chalkiness and The Structural Thermal An...mentioning
confidence: 99%
“…An increase in the number of short chains in amylopectin, crystallinity, and the order of crystallinity, but a decrease in the number of long chains in amylopectin and the ratio of amorphous to ordered starch structure, leads to a deterioration in rice quality by enhancing its chalkiness [11]. In addition, the size distribution of the starch granules is also one of the critical factors affecting rice chalkiness [12]. In a study, scanning electronic microscopy (SEM) observation showed a deficient uniformity and regularity of starch granules, resulting in the altered transmission of light through the endosperm, thereby increasing the CGR and CD [13].…”
Section: Introductionmentioning
confidence: 99%